Liquid-nitrogen-free CTAB DNA extraction method from silica-dried specimens for next-generation sequencing and assembly - Quiñones, Kristine Joyce O.; Gentallan, Renerio P.; Timog, Emmanuel Bonifacio S.; Cruz, Juan Rodrigo A. Vera; Macabecha, Cherray Gabrielle A.; Papa, Irene A.; Coronado, Nadine B.; Bartolome, Michael Cedric B.; Ceribo, Daryl B.; Madayag, Roselle E.; Magtoltol, Jessabel B.; Sienes, Robert Keith A.; et al. (Elsevier, 2024)
Next-generation sequencing requires intact and high-quality DNA. However, typical liquid-nitrogen DNA extraction methods are expensive and not practical for field sample collections. Hence, we present a cost-effective method for DNA extraction from silica-dried leaf samples, eliminating the need for liquid nitrogen. Two protocols were evaluated to determine the effectiveness of grinding dried plant samples without liquid nitrogen in comparison to the standard protocol for tissue homogenization and cell lysis. Protocol 1 involved grinding fresh leaf samples with liquid nitrogen, while Protocol 2 entailed incubating dried plant samples at-20 °C for 1 h before grinding in the absence of liquid nitrogen. Both protocols produced comparable DNA yields with an average A260/A280 ratio of 1.78±0.02, suitable for short- and long-read sequencing. Using Protocol 2, we successfully assembled ten plastomes. It also demonstrated versatility as comparable DNA quality was obtained from dried mollusks and actinomycetes, resulting in the successful assembly of two complete mitochondrial genomes. The protocol is advantageous for research workflows involving the collection of samples in the field as a long-term source of genetic material.